Creating public value through caring for place. (18th January 2018) - Healey, Patsy
Abstract : This essay argues for a relational approach to place qualities and their governance. The argument is developed through a discussion of first, the meaning and significance of place, second, the formation of collective attention, publics and the civil sphere; and third, the challenge of developing moral frames among such publics within which complex judgements about conflicting perceptions and values about place qualities can be situated. Promoting public value through caring for place in this way could act as a significant learning arena for renewing practices of democratic engagement.